An Implicitly Consistent Formulation of a Dual-Mesh Hybrid LES/RANS Method (Communications in Computational Physics, 2018)
A consistent dual-mesh hybrid LES/RANS framework for turbulence modelinghas been proposed recently (H. Xiao, P. Jenny, A consistent dual-mesh frameworkfor hybrid LES/RANS modeling, J. Comput. Phys. 231 (4) (2012)). To betterenforce componentwise Reynolds stress consistency between the LES and the RANSsimulations, in the present work the original hybrid framework is modified to betterexploit the advantage of more advanced RANS turbulence models. In the newformulation, the turbulent stresses in the filtered equations in the under-resolved regionsare directly corrected based on the Reynolds stresses provided by the RANSsimulation. More precisely, the new strategy leads to implicit LES/RANS consistency,where the velocity consistency is achieved indirectly via imposing consistency on theReynolds stresses. This is in contrast to the explicit consistency enforcement in the originalformulation, where forcing terms are added to the filtered momentum equationsto achieve directly the desired average velocity and velocity fluctuations. The newformulation keeps the averaging procedure for the filtered quantities and at the sametime preserves the ability of the original formulation to conform with the physical differencesbetween LES and RANS quantities. The modified formulation is presented,analyzed, and then evaluated for plane channel flow and flow over periodic hills. Improvedpredictions are obtained compared with the results obtained using the originalformulation.